Mapping total microbial communities and waterborne pathogens in household drinking water in China by citizen science and metabarcoding - Wen, Xinyi; Fang, Chutong; Huang, Lihan; Miao, Jiazheng; Lin, Yajuan (Frontiers in Microbiology, 2025)
IntroductionAccess to safe drinking water remains a critical public health priority, as waterborne diseases continue to pose global health risks. In China, microbial contamination in household water supplies is of particular concern. Traditional culture-based monitoring methods are limited in sensitivity and scope, and scaling such efforts nationwide would demand significant resources. Comprehensive, culture-independent microbiome assessments are therefore needed to better characterize microbial risks in tap water.MethodsTo address this gap, we developed a cost-effective, citizen science-based approach for monitoring the tap water microbiome. Between December 2020 and August 2021, 50 household tap water samples were collected by volunteers across 19 provinces and regions in China, including several samples obtained before and/or after extreme weather events including the 2021 Henan Floods and Typhoon In-Fa. A low-biomass sampling protocol was developed and adopted, and DNA was extracted and analyzed via 16S rRNA gene metabarcoding targeting the V4 region.ResultsOf the 50 samples, 22 were successfully amplified and yielded DNA with a significant number of sequencing reads. High-throughput amplicon sequencing identified 7,635 Amplicon Sequence Variants (ASVs), revealing a diverse microbiome in household tap water. Opportunistic pathogens, including Mycobacterium, Acinetobacter, and Legionella, were detected in all PCR-positive samples. Alarmingly, post-typhoon samples from Changzhou showed a marked increase in the relative abundance of Escherichia coli.DiscussionAlthough based on a limited number of sequenced samples, this study highlights potential microbial risks in household tap water, particularly following extreme weather events. The presence of multiple opportunistic and potentially pathogenic taxa underscores the limitations of traditional indicator-based monitoring. Our findings demonstrate the feasibility and scalability of citizen science for microbial water quality survey, offering a complementary tool for national monitoring and informing future public health strategies for water safety.